PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE PADA KINERJA PERUSAHAAN - Clara Risma Alfayanti; Uswatuh Hasanah; Rima E Pratiwi; Windi Amalina; Widya A. P Wardani (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The purpose of this study is to evaluate and analyze the effects of leverage and good corporate governance on the workings of businesses. The study focuses on bank companies that are listed on the Indonesian Stock Exchange (BEI) for the year 2022. The dependent variable in this study is the company's kinerja, which is measured by earnings per share. The independent variable is excellent corporate governance, which is measured by direct deposit; the other independent variable is leverage. This study uses a purposive sampling approach with a sample size of twenty banking companies over a one-year period. The analysis model that is utilized is the Berganda regression analysis. Based on the results of the study, it was determined that the variables Dewan Direksi and Leverage had an impact on the company's kinerja variable simultaneously, the variable Dewan Direksi had an impact on the company's kinerja variable parsially, and the variable Leverage had an impact on the company's kinerja variable parsially but not significantly.